Association of Sympathetic Skin Response with Severity of Diabetic Polyneuropathy (Bangladesh Journal of Neuroscience, 2026)
Background: Diabetes mellitus has emerged as one of the major challenges to human health in the twenty-first century. Diabetic autonomic neuropathy is the least recognized and understood complication of diabetes, but it has a significant negative impact on survival and quality of life.Objective: The objective of this study is to identify the association of sympathetic skin response with severe diabetic polyneuropathy.Materials and Methods: This case-control study was carried out in the Department of Neurology, BSMMU, Dhaka, from May 2022 to September 2023. A total of 64 subjects were enrolled as the study population after satisfying inclusion and exclusion criteria. Among them, 32 were grouped as cases and the rest 32 were control. Toronto Clinical Scoring System (CSS) was used to detect the severity of diabetic polyneuropathy. The SSR was recorded on most standard equipment like NIHON KOHDEN Neuropack MEB-9400 S1 Series EMG/NCV/EP Measuring System in the Department of Neurology, BSMMU.Results: The study included 32 diabetic polyneuropathy patients as cases and 32 age-sexmatched controls. In 7 patients, it showed absent response in both upper and lower limbs. Among the control group, SSR response was present in all populations. There was a significant association between SSR and the severity of DPN.Conclusion: In this study, we found an increased prevalence of delayed and absent SSR in the moderate and severe DPN groups.